2010
DOI: 10.1124/dmd.110.032805
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Binding Cassette B1 Transports Seliciclib (R-Roscovitine), a Cyclin-Dependent Kinase Inhibitor

Abstract: ABSTRACT:Seliciclib, a cyclin-dependent kinase inhibitor, is a promising candidate to treat a variety of cancers. Pharmacokinetic studies have shown high oral bioavailability but limited brain exposure to the drug. This study shows that seliciclib is a high-affinity substrate of ATP-binding cassette B1 (ABCB1) because it activates the ATPase activity of the transporter with an EC 50 of 4.2 M and shows vectorial transport in MDCKII-MDR1 cells, yielding an efflux ratio of 8. This interaction may be behind the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
(36 reference statements)
1
5
0
8
Order By: Relevance
“…In agreement, several studies showed that roscovitine represents a high-affinity substrate of P-gp as well, yet no concomitant ABCB1-mediated resistance could be observed after treatment with roscovitine (26). Noteworthy, roscovitine was also shown to induce apoptosis in a doxorubicinresistant human myeloma cell line that overexpresses Pgp (37). Therefore, we speculate that despite being P-gp substrates, BA-12 and BP-14 do not induce resistance and are thus being promising novel therapeutic agents with persistent antihepatoma activities.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement, several studies showed that roscovitine represents a high-affinity substrate of P-gp as well, yet no concomitant ABCB1-mediated resistance could be observed after treatment with roscovitine (26). Noteworthy, roscovitine was also shown to induce apoptosis in a doxorubicinresistant human myeloma cell line that overexpresses Pgp (37). Therefore, we speculate that despite being P-gp substrates, BA-12 and BP-14 do not induce resistance and are thus being promising novel therapeutic agents with persistent antihepatoma activities.…”
Section: Discussionsupporting
confidence: 68%
“…A few studies used the whole set of in vitro and in vivo tools to address BBB permeability issues [52,78,79]. But only one study has been performed on a sizeable compound set [70].…”
Section: Resultsmentioning
confidence: 99%
“…Росковитин (ROSC, Sigma Aldrich, США) -ингибитор циклинзависимых протеинкиназ -вносили в лунку культурального планшета в конечной концентрации 20 мкМ [10] и инкубировали в течение 18 ч при 37°C и 5% CO 2 . К интактным клеткам линии МСF-7 добавляли культуральную среду в том же объеме, что и ингибитор, и инкубировали в тех же условиях.…”
Section: описание медицинского вмешательстваunclassified